RANCANG BANGUN ALAT PRAKTIKUM KONSTANTA PEGAS DAN FREKUENSI NATURAL DARI PEGAS PUNTIR - Anggakaradewa Nurwibawa Abyantara (2024)
Spring constant and natural frequency practicum equipment are tools used in vibration practicum courses. This tool serves to help students understand the effect of the mass and distance of the mass from the rotation center on the spring constant and the natural frequency of the torsional spring. This study aims to design spring constant and natural frequency practicum tool and also to find out how it works and how to collect data using the practicum tool. Designing process is carried out using CAD applications, where each component is made as accurate as possible so that the practicum tools can work as they should. Practicum equipment components are divided into frames, supports, main bars, weight bars, bearings and weight, these components are then assembled into a single working practicum tool. Data collection was carried out using two different torsional springs with different thicknesses, namely 1mm and 0.8mm. The weight distance is also varied along the weight rod, namely at a distance of 5cm, 10cm, and 15cm from the center of rotation of the main rod, besides that the mass is also varied at 500gram and 1000gram. The experiment results showed that the greater the mass and weight distance from the center of rotation, the greater the constant of the spring, conversely, the smaller the mass and distance of the load from the center of rotation, the greater the natural frequency.